A Note on Estimating the Case Fatality Ratio for Novel Corona Virus Disease (COVID-19) - Swain, Prafulla K. (Coronaviruses, 2021)
Background: In this paper, an attempt has been made to estimate the Case Fatality Ratio (CFR) for coronavirus disease of India and a few selected countries. And also, it highlighted the pros and cons of obtaining crude and adjusted CFR of COVID-19 pandemic. Material and Methods: Data extracted from the WHO situation report and the University of Oxford website have been used for this analysis. The CFR and its 95% confidence interval were computed, trend and bar plot was used for graphical representation. Results: The worldwide crude CFR stands 6.73% (95% CI 6.69 to 6.76) based on 21, 83, 877 confirmed and 1,46,872 death cases(as on 17th April, 2020). Belgium was the highest CFR at 13.95% as compared to others. However, India’s CFR was found to be around 3.26% (as on 17th April, 2020). Conclusion: In conclusion, the estimation and interpretation of CFR are critical in response to ongoing COVID-19. The initial CFR estimates are subject to change, still, it is useful for healthcare planning over the coming months. Moreover, the precise and robust estimates of CFR will be available only at the end of the epidemic.
Keywords: Severe Acute